Antibody Response to HML‐2 May Be Protective in Amyotrophic Lateral Sclerosis. Issue 5 (24th August 2022) - Garcia‐Montojo, Marta; Simula, Elena Rita; Fathi, Saeed; McMahan, Cynthia; Ghosal, Anubrata; Berry, James D.; Cudkowicz, Merit; Elkahloun, Abdel; Johnson, Kory; Norato, Gina; Jensen, Peter; James, Tony; et al.
Abstract : Objectives: Reactivation of HERV‐K(HML‐2) has been found in subsets of individuals with amyotrophic lateral sclerosis (ALS). This study examines the antibody response against HML‐2 in ALS and analyzes its clinical relevance. Methods: Antibodies to HML‐2 envelope (env) were analyzed using a peptide array for epitope mapping and by a peptide enzyme‐linked immunosorbent assay (ELISA) in 242 healthy donors, and 243 ALS and 85 multiple sclerosis (MS) individuals. Extracellular levels of HML‐2 were analyzed by digital polymerase chain reaction (PCR). Results: Antibodies in the sera of ALS individuals recognized more HML‐2 env peptides compared to healthy controls ( p  < 0.0001). ALS individuals had higher levels of HML‐2 than healthy donors ( p  = 0.02) and higher antibody levels against a select HML‐2 env peptide compared to healthy donors or individuals with multiple sclerosis ( p  < 0.0001). 55.14% of ALS compared to 21.16% of healthy donors and 13.10% of MS individuals had antibodies against the HML‐2 peptide (AUC = 0.769, p  < 0.0001). Levels of extracellular HML‐2 DNA in serum ( p  = 0.02) and the number of HML‐2 env peptides recognized by ALS sera ( p  = 0.02) correlated with disease duration. Among ALS individuals, lower levels of HML‐2 antibodies were associated with a definite diagnosis per EL Escorial criteria ( p  = 0.03), and with a lower predicted ( p  = 0.02) and observed survival ( p  = 0.03). Interpretation: There is a differential antibody response against specific epitopes of HML‐2 env in ALS and controls, suggesting epitope spreading, likely due to persistent antigenic exposure following reactivation of the viral genes. Low levels of antibodies to HML‐2 env in ALS are associated with poor prognosis and decreased survival probability. ANN NEUROL 2022;92:782–792